Construction of noise maps with finite elements and newmark - Mantilla, Irla (2012)
This article uses the weak formulation of the problems Partial Hyperbolic type (VPE) for construction noise maps with finite element and Newmark in two-dimensional space. To ensure the numerical simulation of the problem of propagation of the noise source, so that proves the existence and uniqueness of the variational problem in Sobolev spaces evolutionary and applied the finite element method and method Galerkin for spatial discretization and Newmark method for the time discretization. In this work, the innovative technique of preparation of the data base and computational experimentation whit Mathlab, finally obtaining effectively the solution as shown in the convergence of the numerical scheme.